Differentiation of Parkinson’s disease and Parkinsonism predominant multiple system atrophy in early stage by morphometrics in susceptibility weighted imaging - Ren, Qingguo; Wang, Yihua; Xia, Xiaona; Zhang, Jianyuan; Zhao, Cuiping; Meng, Xiangshui (Frontiers in Human Neuroscience, 2022)
Background and purpose: We previously established a radiological protocol to discriminate Parkinsonism-predominant multiple system atrophy (MSA-P) from Parkinson’s disease (PD). However, we do not know if it can differentiate early-stage disease. This study aimed to investigate whether the morphological and intensity changes in susceptibility weighted imaging (SWI) of the lentiform nucleus (LN) could discriminate MSA-P from PD at early stages. Methods: We retrospectively enrolled patients with MSA-P, PD and sex- and age-matched controls whose brain MRI included SWI, between January 2015 and January 2022 at the Movement Disorder Center. Two specialists at the center reviewed the medical records and made the final diagnosis, and two experienced neuroradiologists performed MRI analysis, based on a defined and revised protocol for conducting morphological measurements of the LN and signal intensity. Results: Nineteen patients with MSA-P and 19 patients with PD, with less than two years of disease duration, and 19 control individuals were enrolled in this study. We found that patients with MSA-P presented significantly decreased size in the short line (SL) and corrected short line (cSL), ratio of the SL to the long line (SLLr) and corrected SLLr (cSLLr) of the LN, increased standard deviation of signal intensity (SIsd_LN, cSIsd_LN) compared to patients with PD and controls (P < 0.05). With ROC analysis, this finding had a sensitivity of 89.5% and a specificity of 73.7% to distinguish MSA-P from PD. Conclusions: Compared to PD and controls, patients with MSA-P are characterized by a narrowing morphology of the posterior region of the LN. Quantitative morphological changes provide a potential marker for differentiating MSA-P from PD at early stages.